The sensory dimension of tourist experiences: capturing meaningful sensory-based themes in Southwest Portugal - Agapito, Dora (2014)
Sensory aspects of destinations have recently been in focus as an important dimension in the process of facilitating positive tourist experiences. The countryside embraces local resources rich in multi-sensory stimuli that could be utilized in the planning and marketing of appealing tourist experiences addressed to segments of tourists, while fitting sustainable local development. This study follows a holistic approach to the five external human senses, aiming to capture meaningful sensory-informed themes adequate for segmenting rural tourists. A self-administered survey in four languages was collected from 181 tourists in Southwest Portugal. A multiple correspondence analysis suggests four sensory-informed themes, tentatively named generic beach-related experience, nature-based experience, balanced experience, and rural experience. The proposed themes correspond to a four-solution cluster of tourists presenting different profiles. The largest segment (73 tourists) corresponds to the rural experience, regarding which tourists mainly refer to the taste of local food and the smell of fresh air.